2023
DOI: 10.1108/meq-01-2023-0025
|View full text |Cite
|
Sign up to set email alerts
|

The dilemmas of relevance: exploring the role of natural resources and energy consumption in managing climate crisis in Africa

Abstract: PurposeThe study examines the role of natural resources (NRs) and energy consumption in managing the climate crisis in Africa, using annual series data from the World Bank from 1980 to 2019.Design/methodology/approachThe empirical strategy is based on the second-generation panel techniques that account for cross-sectional dependency in the series. Specifically, the empirical evidence is based on the Westerlund (2017) panel cointegration test, panel augmented mean group, common correlated effects mean group and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 80 publications
(123 reference statements)
0
4
0
Order By: Relevance
“…The ECCB is a sign of a proclivity for environmentally conscious behavior (Straughan and Roberts, 1999;Sajid et al, 2022;Tarifa-Fern andez et al, 2023) which influences consumer's behavioral inclination (Bala et al, 2023;Stadtler and Lin, 2017). It is easy to assess the tendency of ECCB than successful green purchasing behavior and sustainable consumption (Zhang et al, 2023;Anwar et al, 2023;Ghaffar et al, 2023;Shobande and Asongu, 2023). The role of gender moderation in the link between ECCB and the desire to use renewable resources (Martins and Viegas, 2015) and age in the relationship between perceived consumer effectiveness and ECCB (Yahaya et al, 2012) was found significant.…”
Section: Moderation Of Ecologically Conscious Consumer Behaviormentioning
confidence: 94%
See 3 more Smart Citations
“…The ECCB is a sign of a proclivity for environmentally conscious behavior (Straughan and Roberts, 1999;Sajid et al, 2022;Tarifa-Fern andez et al, 2023) which influences consumer's behavioral inclination (Bala et al, 2023;Stadtler and Lin, 2017). It is easy to assess the tendency of ECCB than successful green purchasing behavior and sustainable consumption (Zhang et al, 2023;Anwar et al, 2023;Ghaffar et al, 2023;Shobande and Asongu, 2023). The role of gender moderation in the link between ECCB and the desire to use renewable resources (Martins and Viegas, 2015) and age in the relationship between perceived consumer effectiveness and ECCB (Yahaya et al, 2012) was found significant.…”
Section: Moderation Of Ecologically Conscious Consumer Behaviormentioning
confidence: 94%
“…, 2023; Ghaffar et al. , 2023; Shobande and Asongu, 2023). The role of gender moderation in the link between ECCB and the desire to use renewable resources (Martins and Viegas, 2015) and age in the relationship between perceived consumer effectiveness and ECCB (Yahaya et al.…”
Section: Theoretical Foundation Literature and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations